Antibiotics-encapsulated nanoparticles as an antimicrobial agent in the treatment of wound infection - Taheri, Mohammad; Arabestani, Mohammad Reza; Kalhori, Fereshte; Soleimani Asl, Sara; Asgari, Masoumeh; Hosseini, Seyed Mostafa (Frontiers in Immunology, 2024)
Disruption in the wound-healing process is caused by the presence of bacteria and leads to major problems and delays in wound healing. The limitations of commonly used medicines for treating wound infections include drug toxicity, insufficient microbial coverage, poor penetration, and increased resistance. This study aimed to determine the effect of ciprofloxacin loaded in solid lipid nanoparticles (Cip-SLN) on Pseudomonas aeruginosa and ampiciliin-vancomycin loaded in solid lipid nanoparticles (Amp- Van-SLN) on Staphylococcus aureus in wounds. Antibiotics were encapsulated in SLNs using the double emulsion method and were characterized. The in-vitro effect of antibiotic-loaded nanoparticles on P. aeruginosa and S. aureus was assessed using well diffusion and MIC methods. Finally, the topical antibacterial activity of these nanoparticles against bacterial wound infection was measured in a mouse model. MIC results showed that in the first 24 hours, the free drug had a greater effect on inhibiting bacteria, and in 72 hours, the inhibitory effect of nanoparticles increased. There was no toxicity effect of 400 µg/mL of nanoparticles on cells. According to the findings, the groups treated with Cip-SLN and Amp-Van-SLN were more effective than the control group (untreated) in different concentrations. In the wound healing process, the group treated with solid lipid nanoparticles (SLNs) exhibited a greater epithelial thickness, indicating enhanced healing, compared to the group treated with the free drug. The use of SLN can increase the accumulation of antibiotics at the site of infection with a slow release of the drug due to its fatty nature, which leads to a significant inhibitory effect on bacteria and also improves wound healing.